Sunset Policy and its Effect on Tax Compliance: Case Study Indonesia - Sylviana Kasim S.Sos. M.Si, Elsie; Arianty S.Sos. M.Si, Fitria; Hikmah S.Si. M.Si, Yulial (International Journal of Engineering and Technology, 2018)
Indonesia has several times conducted Tax Amnesty as an effort to pursue the target of increasing tax revenue. One of the Tax Amnesty ever conducted by Indonesia is Sunset Policy which is giving the elimination of administrative sanction. It cannot be denied that Sunset Policy will result in an increase in tax compliance in the short term. This research will look at the long-term impact of Sunset Policy in Indonesia by using Seasonal Autoregressive Integrated Moving Average (SARIMA). The approach used by the authors in this study is a quantitative approach that is a descriptive analysis. The data obtained is secondary data in the form of monthly data receipt of Personal Income Tax from 2004 to 2012 which can be used as a review and researcher base to analyze the effect of Sunset Policy on tax compliance level in Indonesia. Based on the data processing, the results obtained that Sunset Policy affected tax compliance in the year of the issuance of Sunset Policy. However, in the following years after the Sunset Policy is no longer valid, the policy still has a significant effect on tax compliance. Post-Sunset Policy the government does not issue a special policy in order to enforce the law.Â Â